Selective Catalytic Reduction of NOx using Hydrocarbon - Yadav, Deepak (IIT(BHU), Varanasi, 2018)
Abstract is available in the attachment
This thesis submitted by PhD. Scholar IIT(BHU), Varanasi. & supervised by Prof, R. Prasad.
Keywords: Catalytic; Reduction; Hydrocarbon